2022
DOI: 10.3390/ijerph19042388
|View full text |Cite
|
Sign up to set email alerts
|

Health Behaviours and the Sense of Optimism in Nursing Students in Poland, Spain and Slovakia during the COVID-19 Pandemic

Abstract: (1) The COVID-19 outbreak brought about several socio-economic changes and has had a negative impact on the mental health of people around the world. The aim of this study was to examine the correlation between health behaviours and dispositional optimism among nursing students in Poland, Spain and Slovakia during the COVID-19 pandemic. (2) The study was carried out in spring 2021 on a group of 756 nursing students in Poland (n = 390), Spain (n = 196) and Slovakia (n = 170). The diagnostic survey method was ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…This study's findings indicate that nearly half of the respondents (48.43%) had scores indicating a low intensity of general health behaviours, which may provide grounds for further studies on the factors that stimulate individuals to take up health behaviours (so-called "health-related motives"). Students from Spain and Slovakia participating in a different study on health behaviours had a higher percentage of results at a higher level than students from Poland [25]. When comparing the current results with the data gathered by other authors on health behaviours, a certain differentiation can be observed.…”
Section: Discussionsupporting
confidence: 58%
“…This study's findings indicate that nearly half of the respondents (48.43%) had scores indicating a low intensity of general health behaviours, which may provide grounds for further studies on the factors that stimulate individuals to take up health behaviours (so-called "health-related motives"). Students from Spain and Slovakia participating in a different study on health behaviours had a higher percentage of results at a higher level than students from Poland [25]. When comparing the current results with the data gathered by other authors on health behaviours, a certain differentiation can be observed.…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, Sakellari et al investigated the correlation between health behaviors and dispositional optimism among nursing students in Poland, Spain, and Slovakia during the COVID-19 pandemic. This study showed that characteristic optimism is an important predictor of students' health behaviors (40). Further studies have reported that extra-curricular activities such as membership in hobbies clubs, cultural clubs, and sports clubs were shown to play a key role in developing interest and reducing stress in a student's life (35,36).…”
Section: Discussionmentioning
confidence: 73%
“…This study is part of an international research project executed within the framework of one of the researcher’s (E.K.) scientific internship programme [ 28 , 32 ]. This project was given a favourable opinion (No.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 756 nursing students participated in the study, including 390 in Poland (51.59%), 196 in Spain (25.93%) and 170 in Slovakia (22.49%) [ 28 , 32 ]. The mean participant age was 21.20 years (SD = 1.97).…”
Section: Methodsmentioning
confidence: 99%